Combined therapies with nanostructured carbon materials: there is room still available at the bottom. Issue 14 (14th March 2018) - Biagiotti, Giacomo; Fedeli, Stefano; Tuci, Giulia; Luconi, Lapo; Giambastiani, Giuliano; Brandi, Alberto; Pisaneschi, Federica; Cicchi, Stefano; Paoli, Paolo
Abstract : Combining therapies on a sheet of carbon is possible! Abstract : The progress of the chemistry of carbon nanotubes (CNT) and graphene derivatives [mainly graphene oxide (GO)] has produced a number of technologically advanced drug delivery systems (DDS) that have been used in the field of nanomedicine, mostly in studies related to oncology. However, such a demanding field of research requires continuous improvements in terms of efficiency, selectivity and versatility. The loading of two, or more, bioactive components on the same nanoparticle offers new possibilities for treating cancer, efficiently addressing issues related both to biodistribution and pharmacokinetics. Nanostructured carbon materials (NCM), with their high surface area, their efficient cellular membrane crossing and their chemical versatility are ideal candidates for easy hetero-decoration and exploitation as advanced DDS. This review describes the achievements obtained in this area focusing on those studies in which two or more active components were loaded onto the DDS.